Perancangan Sistem Informasi Verifikasi Klaim Rawat Jalan BPJS Kesehatan - Phatonah, Ike Siti; Syahidin, Yuda; Gunawan, Erix (Program Studi Teknik Informatika Universitas Pamulang, 2024)
There has been a sea shift in health services brought about by the development of ICT, and not only in the way health information systems are run. The primary objective of this study was to gather requirements for a Microsoft Visual Studio 2010-based outpatient claims verification information system for BPJS health. We need a reporting information system that uses computerization to decrease service delays, and the existing reporting system implementation is the key cause for it. While the development technique employs the waterfall methodology, the research method applies a descriptive qualitative approach. The result of the applied system design is in the form of an outpatient BPJS file claim verification report. With the design of this system, it can be a proposal and can be implemented by Muhammadiyah Bandung Hospital to facilitate the process of reporting outpatient BPJS file claims.